EFFECT OF DIGITAL MARKETING RESOURCES ON THE FIRM GROWTH - Tamma Elhachemi (International Journal of Innovations in Engineering Research and Technology, 2021)
Marketing strategies had altered with the evolvement of digital marketing in the last 10 years. The world has become digital now people around the world are connected with social platforms available. Internet and marketing have become an integral part of all organizational marketing plans now a day. Every firm willing to enhance the performance now days is using strong marketing through possible digital platforms. Opportunities always come with challenges; digital marketing is not an exception. There are challenges in achieving success through digital strategies. This paper discusses the impact of digital marketing on the performance of a firm. The survey of small scale firms is carried out using social media and the conclusions on the findings are presented.